Online Grocery Shopping Intentions: A Comparative Study between Gen Millenials and Gen Z in Indonesia - Felicia Vionita; Roger Alexsander Siburian (Publikasi Indonesia, 2024)
This study focuses on behavioral intentions in buying groceries Online. This research also aims to compare the factors influencing Gen Millennial and Gen Z consumers. This research applies the Technology Acceptance Model (TAM). The hypotheses used are perceived usefulness, perceived ease of use, and perceived enjoyment of online grocery shopping. This research uses a survey to collect data from 199 respondents, 98 are millennials and 101 are Gen Z in Indonesia. The results showed that perceived usefulness and perceived enjoyment have a significant effect on online grocery shopping intentions in Gen Millennials and Gen Z, while perceived ease of use only affects online grocery shopping intentions in Gen Millennials.